Alternative Feed Use in Poultry Chickens: Impacts on Feed Efficiency and Physiological Parameters—A Systematic Literature Review - Oktariansyah, Yadi; Kamal, Mustafa (Mahesa Research Center, 2026)
Feed cost and supply instability remain major constraints in poultry production, particularly in smallholder and semi-intensive systems where local chickens are commonly raised. Alternative feeds derived from local resources and agro-industrial by-products have been promoted to reduce reliance on commercial rations, yet evidence regarding their effects on feed efficiency and physiological stability remains inconsistent. This systematic literature review synthesized controlled feeding trials evaluating the effects of alternative feeds on feed conversion ratio (FCR), growth performance, and physiological parameters in poultry chickens. A PRISMA-guided search was conducted using Scopus, Web of Science, PubMed, and Google Scholar, and 20 eligible studies were included in the qualitative synthesis. Evidence was categorized into agro-industrial by-products, plant leaf meals, high-fiber ingredients, fermented feeds, animal-based alternative proteins, antinutrient-rich plants, enzyme-supported diets, hybrid feeding strategies, and layer-phase alternative feeding. Feed efficiency responses were highly context-dependent. Neutral or improved FCR and stable growth were more likely when alternative feeds were used at moderate inclusion levels and supported by fermentation, enzyme supplementation, and adequate micronutrient premixes. In contrast, high inclusion of fibrous or antinutrient-rich ingredients frequently reduced efficiency and increased the risk of metabolic stress. Hybrid feeding strategies produced the most consistent outcomes.